Rivaling paradigms in psychiatric neurosurgery: adjustability versus quick fix versus minimal-invasiveness - Müller, Sabine; Riedmüller, Rita; van Oosterhout, Ansel (Frontiers in Integrative Neuroscience, 2015)
In the wake of deep brain stimulation (DBS) development, ablative neurosurgical procedures are seeing a comeback, although they had been discredited and nearly completely abandoned in the 1970s because of their unethical practice. Modern stereotactic ablative procedures as thermal or radiofrequency ablation, and particularly radiosurgery (e.g., Gamma Knife) are much safer than the historical procedures, so that a re-evaluation of this technique is required. The different approaches of modern psychiatric neurosurgery refer to different paradigms: microsurgical ablative procedures is based on the paradigm ‘quick fix,’ radiosurgery on the paradigm ‘minimal-invasiveness,’ and DBS on the paradigm ‘adjustability.’ From a mere medical perspective, none of the procedures is absolutely superior; rather, they have different profiles of advantages and disadvantages. Therefore, individual factors are crucial in decision-making, particularly the patients’ social situation, individual preferences, and individual attitudes. The different approaches are not only rivals, but also enriching mutually. DBS is preferable for exploring new targets, which may become candidates for ablative microsurgery or radiosurgery.